2015
DOI: 10.1007/s00424-015-1748-7
|View full text |Cite
|
Sign up to set email alerts
|

Corticomedullary difference in the effects of dietary Ca2+ on tight junction properties in thick ascending limbs of Henle’s loop

Abstract: The thick ascending limb of Henle's loop (TAL) drives an important part of the reabsorption of divalent cations. This reabsorption occurs via the paracellular pathway formed by the tight junction (TJ), which in the TAL shows cation selectivity. Claudins, a family of TJ proteins, determine the permeability and selectivity of this pathway. Mice were fed with normal or high-Ca(2+) diet, and effects on the reabsorptive properties of cortical and medullary TAL segments were analysed by tubule microdissection and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
81
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(86 citation statements)
references
References 42 publications
5
81
0
Order By: Relevance
“…As recently reported, claudin expression differs along the corticomedullary axis of the TAL (10). Whereas TJ expression of cldn16 and cldn19 is confined to the cortex and the outer stripe of outer medulla (OSOM), cldn10b is expressed within TJs along the entire TAL from the cortex to the inner stripe of outer medulla (ISOM).…”
Section: Significancementioning
confidence: 80%
See 4 more Smart Citations
“…As recently reported, claudin expression differs along the corticomedullary axis of the TAL (10). Whereas TJ expression of cldn16 and cldn19 is confined to the cortex and the outer stripe of outer medulla (OSOM), cldn10b is expressed within TJs along the entire TAL from the cortex to the inner stripe of outer medulla (ISOM).…”
Section: Significancementioning
confidence: 80%
“…Whereas cldn3, cldn10, cldn16, and cldn19 were clearly expressed, cldn11 could not be detected. The anti-cldn10 antibody cannot discriminate between isoforms a and b, but PCR showed that only cldn10b is present in the TAL (10,12). Thus, a positive cldn10 staining in the TAL is considered to indicate the presence of the isoform cldn10b.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations